Changes in driving stresses and horizontal surface velocity on Hellstugubreen, Jotunheimen, Norway : an investigation of inter-decadal fluctuations - Pay, Ingeborg (NTNU, 2014)
The study of dynamics is crucial to the understanding of how a glacier responds to fluctuations in climate. The driving forces behind glacier flow are determined by ice thickness and surface slope. A multi-dataset approach was used to determine these factors for Hellstugubreen, a small (3.38 km2 in 2009) valley glacier located on the west-east water divide in the Jotunheimen region of south-western Norway, between 1941 and 2009. Maps for the glacier exist from the 1940s onwards and it has long records of frontal changes, velocity and mass balance data. The most recent DEM was created from LiDAR data, while the DEMs for the older maps were genereated from the contour lines. Volume changes and surface slope were computed by subtracting the DEMs. Between 1941 and 2009, Hellstugubreen lost 58% of its mass (the equivalent of a 20 m water layer) and saw its extent reduced by 20%. Losses have been constant, with the exception of a slight advance and volume gain in the 1990s. Hellstugubreen behaved according to its location on the west-east profile in the region, and its volume and frontal have fluctuated in line with other glaciers in the area. It was found that both local and global (NAO) climate influence the ice mass. The compared stakes for the different datasets show an increase in the angle of the surface slope, but no spatial pattern could be established in these changes. Changes in ice thickness were determined by combining the DEMs with interpolated data obtained during an echo sounding survey in 2011. Thus, driving stresses could be computed for selected stakes. With great fluctuations in both ice thickeness and slope, driving stresses have changed considerably, from -50% to 45% between 1941 and 2009. During the same period, Hellstugubreen’s average annual surface velocity increased by 15%, from 8.14 m yr-1 in 1941 to 9.53 m yr-1 in 2009. However, the differences in average daily velocity are too small to be statistically significant. The steepening of the surface could have countered the effects from the ice ...